Designing Information Provision Experiments - Ingar Haaland; Christopher Roth; Johannes Wohlfart (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2020)
We review methodological questions relevant for the design of information provision experiments. We first provide a literature review of major areas in which information provision experiments are applied. We then outline key measurement challenges and design recommendations that may be of help for practitioners planning to conduct an information experiment. We discuss the measurement of subjective beliefs, including the role of incentives and ways to reduce measurement error. We also discuss the design of the information intervention, as well as the measurement of belief updating. Moreover, we describe ways to mitigate potential experimenter demand effects and numerical anchoring arising from the information treatment. Finally, we discuss typical effect sizes in information experiments.
Keywords: C90; D83; D91; L82; 330; Experimental Design; Beliefs; Information; Obfuscation